Assessing the Global Operational Footprint of Higher Education with Environmentally Extended Global Multiregional Input‐Output Models. (29th January 2016) - Lang, Tim; Kennedy, Christopher
Summary: This study used two recently developed environmentally extended global multiregional input‐output models (EE GMRIOs)—WIOD and EXIOBASE—to assess the global operational footprint of higher education for five impact categories: energy, water, material, and land use, and carbon dioxide (CO2 ) emissions. The results of our analysis showed that, in 2009, the global environmental impacts attributable to education as a fraction of total global environmental impacts were not more than 2.5% of energy use and CO2 emissions, and not more than 1.5% of material, water, and land use—the vast majority of impacts generated upstream. These fractions have increased moderately since 1995, potentially driven by increased tertiary enrollment as a fraction of overall enrollment. Analysis of data from the year 2000 showed that, at most, an additional 0.15% for each impact category was attributable to research and development specifically. Inter‐regional and sectoral dynamics were also explored. Europe and the Organization for Economic and Cooperative Development (OECD) had lower total impacts than the rest of world, but their intensities per student were greater. Europe and the OECD also disproportionately shift their impacts to the rest of world. Purchases from energy and utility sectors contribute most to education‐driven energy usage and CO2 emissions, whereas purchases from food, hospitality, and agriculture sectors contribute most to water and land usage. Materials usage is driven more evenly by all sectors. The study concludes that higher education should place emphasis on addressing upstream impacts and recognize the importance of its role in global sustainability beyond its operational footprint.